Competitive strategy of a construction organization - LESHCHYNSKY , Viktor (Ways to Improve Construction Efficiency, 2025)
The article provides an expanded analysis of the competitive strategy of construction organizations under modern economic conditions characterized by rapid scientific, technological, and managerial transformations. The construction sector today demonstrates accelerated development driven by the introduction of innovative materials, digital tools, and advanced construction technologies, which significantly intensify competition and require companies to revise their strategic priorities. In this context, the study examines contemporary approaches to evaluating the economic position of construction enterprises, identifying the determinants of their competitiveness, and formulating effective strategic models that ensure sustainable development in a dynamic market environment. Particular attention is given to the role of strategic planning in strengthening a company’s market position, optimizing resource allocation, and enhancing responsiveness to changing customer demands and macroeconomic fluctuations. The article emphasizes that the primary mission of any construction organization is not only to satisfy societal needs for high‑quality construction services but also to ensure stable profitability and long‑term financial resilience. Therefore, the ability to accurately assess internal capabilities and external factors becomes a critical component of forming a viable competitive strategy. The research highlights the necessity for construction companies to adapt their competitive behavior to the realities of market volatility, increasing technological complexity, and intensifying competition at both national and international levels. Strategic tools such as market analysis, benchmarking, cost optimization, innovative project management, and customer‑oriented service models are identified as essential elements of competitive advantage. The article concludes that the development and implementation of an effective competitive strategy enable construction organizations to enhance operational efficiency, expand market presence, and maintain competitiveness in rapidly evolving economic conditions.